'I Belong Here; I been Coming a Big Time': An Exploration of Belonging that Includes the Voice of Children. Issue 4 (December 2017) - Wastell, Selma Jo; Degotardi, Sheila
BELONGING, AS A TERM and a concept, has entered popular lexicon and is being extensively referred to in a variety of everyday and academic contexts. The word presumes a shared understanding, yet despite its common usage, theoretical literature suggests that this is not an accurate assumption. This research investigated what belonging meant to a group of young children aged between three and five years in an early care and education service, and the implications of their understandings. The core concepts of belonging to people and to place had been identified in the literature but what emerged was that children identified new elements, which were powerful determinants of belonging for them. The research confirmed that young children are indeed capable of conceptualising and expressing complex cognitive concepts like belonging when provided with a context conducive to this.